The legal effect of a coup d'etat on traditional constitutional concepts - Mkwentla, Nelson Koala (Rhodes University, Faculty of Law, Law, 2002)
This thesis deals with constitutional law and other legal subjects such as Jurisprudence and Judicial Review. One constitution is distinguishable from another by its own provisions. These provisions are usually referred to as either the basic characteristics or features of the particular constitution and these are invariably derived from the basic political philosophy and constitutional arrangements of the particular country. A coup affects these characteristics in different ways. Some automatically disappear as being incompatible with the revolution; some are modified, others are strengthened. The usurpers may choose to set aside the constitution completely and replace it with another, or amend it to suit the new situation, or rule without any constitution. This often happens amidst the rattle of weapons and the whirr of military engines in and around the capital of a given country on that awesome occasion. This thesis sets out to examine the legal aspects of a coup d' etat. The thesis is divided into six broad sections. Part one will deal with the theoretical background. I shall discuss an overview of Kelsen's pure theory of law. The second part deals with the scope of its application in revolutionary situations and will also touch upon the reason behind the Kelsen's theory as shown by decided cases from country to country. The third part deals with the essence as well as the significance of the doctrine of necessity to validate unconstitutional acts in the case of a coup d' etat. This discussion is to pave the way for the fourth part which is to explore the position of judges who took oath of office under the old constitution. I am to explain their position after a coup d' etat. The fifth part forms the gist of my research. I shall examine the effect of a coup d' etat on traditional constitutional concepts such as fundamental rights, separation of powers, rule of law and judicial review in the military regime. The sixth part will deal with African experience. I shall include recommendations and conclusions drawn from the Lesotho and Uganda experiences.
Keywords: Coups d'état; Constitutional law